Performance of Crowdsourcing to Monitor and Filter Relevant S c ien tific L iterature - Granikov, Vera; El Sherif, Reem; Pluye, Pierre (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
With the ever - growing volume of scientific literature, it is challenging for researchers to stay up - to - date. This prospective study aims to engage a heterogeneous group of participants in monitoring and filtering articles on online consumer health information and measure the “crowd’s” performance to determine whether crowdsourcing could be a reliable solution.